Prediction of cardiovascular diseases mortality- and disability-adjusted life-years attributed to modifiable dietary risk factors from 1990 to 2030 among East Asian countries and the world - Nawsherwan; Bin, Wang; Le, Zhang; Mubarik, Sumaira; Fu, Guo; Wang, Yan (Frontiers in Nutrition, 2022)
Background: Unhealthy eating habits are a significant modifiable risk factor for cardiovascular diseases (CVDs); nevertheless, no evidence of their impact on CVD burden has been reported in East Asian countries. We aimed to determine the trend and predict the future CVDs burden attributed to modifiable dietary risk factors in the East Asian countries (China, Japan, South Korea, and North Korea) and the world. Methods: The Global Burden of Disease (GBD) 2019 data were used to find the trend of CVDs (ischemic heart disease (IHD) and ischemic stroke (IS)) mortality and disability-adjusted life-years (DALYs) attributed to dietary risk factors in the East Asian countries and the world (1990-2019) and its prediction from 2020 to 2030. We used the joinpoint regression model and the autoregressive integrated moving average (ARIMA) model for trend and future forecast, respectively. Results: From 1990 to 2019, regardless of the sex, the age-standardized mortality rate (ASMR) and DALYs of IHD attributed to dietary risk factors significantly decreased in Japan, South Korea, and the world. However, the ASMR of IHD significantly increased in Chinese males and for both sexes in North Korea. The ASMR and DALYs of IHD and IS due to dietary risk factors were higher in males than in females in the world. From 2020 to 2030, the ASMR of IHD is predicted to increase in South Korean females and Japanese males. Globally, a diet low in whole grains was the top risk factor of highest IHD mortality and DALYs in 2019, followed by a diet low in legumes and a diet high in sodium. Diet low in whole grains, a diet high in sodium, and a diet low in legumes were the leading risk factors of high IHD mortality in East Asian countries. Conclusion: The trend of IHD and IS burden due to dietary risk factors varies substantially across the East Asian countries compared to the trend of CVDs burden in the world. The study findings may help the public health policymakers to design proper strategies for improvement of the quality of life to combat the CVDs burden in the future for the East Asian countries.